Religious Freedom and the Idea of Establishing Islamic State - Hapsin, Abu (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2017)
The idea of Gamwell on“religion as rational” was based on the concept that religious freedom is nothing other than a political discourse that can be figured out only through a democratic resolution. Changing paradigm from “religion as non-rational” to “religion as rational” is a necessary condition for entering a public debate. Yet, the sole public debate or public view is not enough to solve the modern political problematic. The public debate must be guided by a constitutional procedure affirmed by the body politic so that it fulfills the criteria of formal claim about justice. Applying qualitative research and literature review this research tried to reveal: Gamwell’s idea of religious freedom, the features of the Islamic State as described by Abdul Rauf and Gamwell’s concept of religious freedom and the idea of establishing the Islamic State advocated by Abdul Rauf.Gagasan Gamwell tentang "agama itu rasional" didasarkan pada konsep bahwa kebebasan beragama tidak lain adalah wacana politik yang hanya bisa diraih melalui resolusi demokratis. Mengubah paradigma dari "agama sebagai tidak rasional" menjadi "agama sebagai rasional" adalah syarat yang diperlukan sebelum memasuki debat publik. Namun, debat publik atau pandangan publik saja tidak cukup untuk memecahkan masalah politik modern. Perdebatan publik harus dipandu oleh prosedur konstitusional yang ditegaskan oleh badan politik sehingga memenuhi kriteria klaim formal tentang keadilan. Dengan menggunakan penelitian kualitatif dan kajian pustaka penelitian ini mencoba mengungkapkan: gagasan Gamwell tentang kebebasan beragama, ciri-ciri Negara Islam seperti yang dijelaskan oleh Abdul Rauf, dan konsep Gamwell tentang kebebasan beragama, serta gagasan untuk mendirikan Negara Islam yang dianjurkan oleh Abdul Rauf.